CHALLENGES OF THE CONTINUOUS PROGRESSION SYSTEM IN THE SÃO PAULO STATE PUBLIC SCHOOL SYSTEM - Barbosa, Aline Cristiane [UNESP]; Bertagna, Regiane Helena [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2023)
The objective of this article is to discuss the Continuous Progression regime in the Sao Paulo state public school system, by means of qualitative research, bibliographic and documentary survey. Covering 44 documents from 1995 to 2017, the following were highlighted: Bill 251/2007, which provided for the end of Continuous Progression in the state of SP; Supplementary Law 41/2008, which instituted the Bonus for Results (BR) and Bill 857/2015, which proposed the end of Automatic Approval. The analysis of quantitative data from IBGE showed that there was an increase in the school failure rate between 1999 and 2016, invalidating the claim that the Continuous Progression regime had become the practice of Automatic Promotion. However, the absence of participation in the discussion of the proposal, continuing education for teachers, investment in appropriate materials, discussions about the policy in initial teacher training courses, etc., undermined the implementation of the educational policy.
Keywords: Public Policies in Education; Evaluation of Education; Quality of Education; Elementary Education; Continuous Progression